The role of Mahabbah intellectual stimulation leadership in improving organizational performance - Andini, Rita; Sulistyo, Heru; Nurcholis, Lutfi (Edelweiss Applied Science and Technology, 2024)
This research aims to explore a new conceptual model that can fill the limitations of previous studies and research gaps between organizational learning and organizational innovation which is centered on the concept of mahabbah intellectual stimulation leadership which is expected to encourage increased organizational performance. There are phenomena and research gaps so that a conceptual model is built and a hypothesis is proposed so that the significance of the hypothesis test becomes the basis for answering the research problem. The model produced through the development of organizational learning and organizational innovation based on Mahabbah Intellectual Stimulation Leadership towards improving performance in the Private Higher Education Undergraduate Study Program under the auspices of the Superior Accredited University in LLDIKTI Region VI Central Java is a finding for the novelty of this research. Leadership can be realized through a leadership quality approach, namely Mahabbah Intellectual Stimulation Leadership (MISL), which is a leader’s behavior that encourages subordinates to think creatively and innovatively on the basis of compassion and maintaining harmony within the organization and has the potential to increase intelligence and organizational performance. 130 questionnaires were obtained from the Head of the Study Program. Data collection was carried out using a sampling method using proportionate stratified random sampling technique. Model and hypothesis testing was carried out using structural equation modeling (SEM) analysis with AMOS software. The existence of mahabbah intellectual stimulation leadership is an important concept regarding leadership that encourages organizational innovation towards organizational performance. This study develops a new leadership model based on compassion and harmonization based on Islamic values, namely Mahabbah Intellectual Stimulation Leadership. Next, test the relationship of this new concept to organizational learning, organizational innovation and ultimately to improving organizational performance (organizational performance) in the Private Higher Education Undergraduate Study Program under the auspices of the Superior Accredited University in LLDIKTI Region VI, Central Java.